Resiliensi Istri Korban KDRT: Faktor Mempertahankan Keutuhan Keluarga - Atika Nur Ismalia; Siti Komariah; Rika Sartika (Ideas Publishing, 2022)
This research begins with an incident related to the problem of domestic violence. The acts of violence that occur are dominated by wives as victims. Even though there is violence, the wife of the victim of domestic violence chooses to survive rather than divorce. The decision is because the wife has the ability to rise from adversity which is called resilience. The resilience that occurs in the wife is influenced by various internal and external factors. The purpose of this research is to describe the factors of surviving wives which can be explained thoroughly to help other women be able to and overcome problems in the family sphere. Using a qualitative approach with case study methods and data collection techniques used in the form of observation, interviews, and documentation. The results of this study stated that the wifes survival factor was caused by internal factors such as still having feelings, and spirituality and external factors such as children, negative community stigma, economy, children, and social support.